Creatinine related reference ranges for urinary homovanillic acid and vanillylmandelic acid at 6 months of age. Issue 3 (March 1993) - Cole, M; Parker, L; Craft, A W; Bell, S; Dale, G; McGill, A C; Seviour, J A; Smith, J
Abstract : The relationship between homovanillic acid (HVA), vanillylmandelic acid (VMA), and creatinine in the urine of 6 month old babies has been studied and reference ranges in the form of centiles constructed for HVA and VMA against creatinine. Over 10, 000 urine samples were collected from babies in four health districts in the north of England. HVA and VMA concentration, either independently or when divided by creatinine concentration, were dependent upon the absolute concentration of creatinine in the sample. After adjustment for creatinine significant differences in the mean concentration of HVA were found between sexes. No such differences were found for VMA. HVA and VMA were also found to be age dependent. Centiles were constructed using a procedure which makes no distributional assumptions about the data. The net effect of utilising these centiles was to increase the predictive value of a positive screening test from 20% to 40% without any increase in the false negative rate.